2016
DOI: 10.1075/lab.14024.don
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of interrogative use in near-native French

Abstract: This paper reports on interrogative (question) use in the informal spontaneous speech of near-native second-language French speakers. Interrogatives present considerable variation in French, and choices of interrogative form depend on semantics, communicative function, and register. Using a corpus of spontaneous conversations between near-native (NNSs) and native speakers (NSs), the inventory of interrogatives used is described; A detailed examination is then given of the question marker est-ce que ("is it tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 41 publications
2
20
0
1
Order By: Relevance
“…Our primary goals are to examine the linguistic and sociostylistic constraints that condition NNSs' use of future-time expression in French and to compare their variable use to that of NSs with whom the NNSs have close relationships. 2 As a secondary goal we briefly compare our results on future-time expression to findings from previous investigations that have examined how the same group of NNSs uses other variable structures (Donaldson, 2016(Donaldson, , 2017. In so doing, we argue for the importance of multiple, complementary investigations of a single group of participants for advancing knowledge of sociolinguistic competence.…”
Section: Near-native Sociolinguistic Competence In French: Evidence Fmentioning
confidence: 84%
See 3 more Smart Citations
“…Our primary goals are to examine the linguistic and sociostylistic constraints that condition NNSs' use of future-time expression in French and to compare their variable use to that of NSs with whom the NNSs have close relationships. 2 As a secondary goal we briefly compare our results on future-time expression to findings from previous investigations that have examined how the same group of NNSs uses other variable structures (Donaldson, 2016(Donaldson, , 2017. In so doing, we argue for the importance of multiple, complementary investigations of a single group of participants for advancing knowledge of sociolinguistic competence.…”
Section: Near-native Sociolinguistic Competence In French: Evidence Fmentioning
confidence: 84%
“…Afin de comprendre ce cas de variation, nous faisons appel à des facteurs linguistiques qui ont été identifiés dans des recherches précédentes, et nous proposons un nouveau facteur qui nous permet d'étudier le rôle joué par la formalité des variantes dans l'expression du futur. Pour conclure, nous comparons les résultats de cette analyse aux recherches précédentes qui ont examiné d'autres structures variables dans le même corpus (notamment, la négation et les interrogatives, Donaldson, 2016Donaldson, , 2017 et nous soulignons l'intérêt et l'importance de faire de multiples analyses complémentaires d'un seul corpus.…”
Section: Résuméunclassified
See 2 more Smart Citations
“…As final rises (H%) are used in French and German to signal interrogativity, German learners might tend to generalize the H% pattern (and the marker ECQ) for all types of questions -in spite of the pragmatic differences between and the alluded intonational variability in both languages (see studies on interrogatives and their prosody in L2: [21], [22], [23] Earlier research on L2 intonation has shown that learner data are characterized by a narrower pitch range and a lower degree of F0 variability (see [24] for L2 French read data produced by German learners). The same holds true for speech rate: L2 speech is known to be typically slower than L1 speech ( [25]).…”
Section: Aims and Hypothesesmentioning
confidence: 99%